Perioperative Complications in Posterior Surgeries for Cervical Ossification of the Posterior Longitudinal Ligament: A Prospective Nationwide Investigation. Issue 10 (December 2021) - Yoshii, Toshitaka; Egawa, Satoru; Sakai, Kenichiro; Kusano, Kazuo; Nakagawa, Yukihiro; Hirai, Takashi; Wada, Kanichiro; Katsumi, Keiichi; Fujii, Kengo; Kimura, Atsushi; Furuya, Takeo; Nagoshi, Narihito; et al.
Abstract : Study Design: This was a prospective multicenter study. Objective: The aim of this study was to investigate the perioperative complications of posterior surgeries for the treatment of cervical ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: Surgical treatment for cervical OPLL has a high risk of various complications. Laminoplasty (LAMP) and posterior decompression and instrumented fusion (PDF) are effective for multilevel cervical OPLL; however, few studies have focused on the surgical complications of these 2 procedures. Materials and Methods: We prospectively included 380 patients undergoing posterior surgeries for cervical OPLL (LAMP: 270 patients, PDF: 110 patients), and investigated the systemic and local complications, including neurological complications. We further evaluated risk factors related to the neurological complications. Results: Motor palsy was found in 40 patients (10.5%), and motor palsy in the upper extremity was most frequent (8.9%), especially in patients who received PDF (14.5%). Motor palsies involving the lower extremities was found in 6 patients (1.6%). Regarding local complications, dural tears (3.9%) and surgical site infections (2.6%) were common. In the univariate analysis, body mass index, preoperative cervical alignment, fusion surgery, and the number of operated segments were the factors related to motor palsy. Multivariate analysis revealed that fusion surgery and a small preoperative C2−C7 angle were the independent factors related to motor palsy. Motor palsy involving the lower extremities tended to be found at early time points after the surgery, and all the patients fully recovered. Motor palsy in the upper extremities occurred in a delayed manner, and 68.8% of patients with PDF showed good recovery, whereas 81.3% of patients with LAMP showed good recovery. Conclusions: In posterior surgeries for cervical OPLL, segmental motor palsy in the upper extremity was most frequently observed, especially in patients who received PDF. Fusion and a small preoperative C2−C7 angle were the independent risk factors for motor palsy. Level of Evidence: Level III.